PERAN KEPEMIMPINAN, ETOS KERJA, DAN PERSEPSI KEPALA SEKOLAH TERHADAP MUTU PENDIDIKAN - Musadad, Akhmad Arif (Universitas Sebelas Maret, 2010)
This research aims to: (1) find out the description of (a) principal's leadership,(b) work ethos, (c) perception on the teacher's teaching capability, and (d) quality ofElementary School; (2) develop and examine the effect of principal's leadership, workethos, perception of the teacher's teaching capability directly or indirectly on educationquality. This research was conducted at the elementary schools in Surakarta from Marchto September 2004. The research method employed was a descriptive correlation methodthat is expost facto in nature. The population was the principals of elementary schoolsthroughout Surakarta city. 37 respondents were selected as the sample using clusterrandom sampling technique. The instrument of data collection employed was questionnairewith Likert scale for dependent variable: education quality (Y); independentvariable: principal's leadership (X1), work ethos (X2); and mediating variable: perceptionof the teacher's teaching capability (X3). Technique of analyzing data employed wasstatistic technique with correlation regression and path analysis. From the result ofresearch, it can be concluded that: (1) the principal's leadership, work ethos, perceptionon the teacher's teaching capability, and education quality (elementary school) have apositive and significant relation; (2) there is a direct positive significant effect of principal'sleadership factor on the quality of education with effective contribution 26.57%;(3) there is a direct positive significant effect of principal's work ethos factor on thequality of education with effective contribution 24.68%; and (4) there is a direct positivesignificant effect of principal's perception of the teacher's teaching capability factor onthe quality of education with effective contribution 24.57%.